Illustrated dictionary of architecture - Burden, Ernest E., 1934- (New York : McGraw-Hill, 2012)
Meticulously written, heavily cross-referenced, and filled with more than 3000 new and updated definitions and 1,000 new photographs, this impressive, visual resource is the best way to gain a full understanding of architectural elements and the new language of green and sustainable architecture.--BACK COVER.
Previous ed.: 2002.
Keywords: Architecture -- Dictionaries